2018
DOI: 10.3892/ijmm.2018.3882
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-552 promotes hepatocellular carcinoma progression by downregulating WIF1

Abstract: MicroRNAs (miRNAs/miRs) are involved in the metastasis of hepatocellular carcinoma (HCC). In the present study, it was demonstrated that miR-552 was upregulated in HCC tissues. High miR-552 expression was associated with malignant clinicopathological features and decreased survival rates. The in vitro results indicated that miR-552 overexpression promoted migration, invasion and epithelial-mesenchymal transition in Hep3B cells. However, the knockdown of miR-552 inhibited its oncogenic roles in Huh-7 cells. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Comparing miR-552 expression in 158 pairs of colon cancer (CC) adenocarcinoma tissues with proficient DNA mismatch repair (pMMR) and adjacent tissues found that miR-552 expression was significantly associated with CC risk [20]. In liver cancer (HCC), Qu W et al detected the expression levels of miR-552 in 81 pairs of HCC tissues and adjacent non-tumor tissues and found that miR-552 expression levels in HCC tissues were increased [3], which was found in the other two independent studies [26,27]. Han T et al found that miR-552 was overexpressed in liver tumor-initiating cells (T-ICs) [28].…”
Section: The Clinical Significance Of Mir-552 In Human Cancermentioning
confidence: 82%
See 4 more Smart Citations
“…Comparing miR-552 expression in 158 pairs of colon cancer (CC) adenocarcinoma tissues with proficient DNA mismatch repair (pMMR) and adjacent tissues found that miR-552 expression was significantly associated with CC risk [20]. In liver cancer (HCC), Qu W et al detected the expression levels of miR-552 in 81 pairs of HCC tissues and adjacent non-tumor tissues and found that miR-552 expression levels in HCC tissues were increased [3], which was found in the other two independent studies [26,27]. Han T et al found that miR-552 was overexpressed in liver tumor-initiating cells (T-ICs) [28].…”
Section: The Clinical Significance Of Mir-552 In Human Cancermentioning
confidence: 82%
“…In HCC cells, miR-552 increased the expression level of E-cadherin and down-regulated the expression of N-cadherin and vimentin by down-regulating the expression of AJAP1 [3]. In the HCC HIF3B cell line, miR-552 could down-regulate WIF1 expression, increase the effect of E-cadherin, and promote the EMT pathway [27]. miR-552 can target RUNX3 by inhibiting miR-186/E-cadherin/ EMT pathway, thereby promoting cell migration and invasion of HCC cells [26,57].…”
Section: Emtmentioning
confidence: 97%
See 3 more Smart Citations